EFEKTIVITAS BIMBINGAN KELOMPOK TEKNIK PROBLEM SOLVING UNTUK MENINGKATKAN KECERDASAN SOSIAL SISWA - Desiree Deffia Murti, Nisrina; Yuwono Puji Sugiharto, Dwi; Nurul Amin, Zakki (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Adolescents during their development are required to have good social intelligence to be able to establish relationships and adapt to their social environment, however, this low social intelligence is reflected in the high rate of violence and bullying in schools as a manifestation of individual failure to understand, empathize, and manage relationships with others. The study was conducted to determine the effect of group guidance services with problem-solving techniques to improve social intelligence. This study applied a quantitative approach using an experimental research method of one-group pre-test post-test design. The intervention was given to a group of 7 students with low social intelligence, which was measured using a Likert scale instrument that had been tested for validity and reliability. The intervention was carried out in 5 sessions with a duration of 70-90 minutes per session using problem-solving stages, which included identifying and formulating the problems faced, analyzing the problems, formulating temporary assumptions or hypotheses, collecting relevant data or information, and compiling recommendations as the most appropriate alternative solutions to the problem. Data analysis used a paired sample t-test, with the results showing an increase in social intelligence scores after the intervention with a significance value of p < 0.05. The hypothesis of this study was that there would be a difference in students' social intelligence levels before and after receiving problem-solving group guidance services. However, the small sample size limits the generalizability of the results. This study suggests that problem-solving group guidance services can be an alternative intervention to help students improve their social intelligence.